Structural performance of steel plates - Musmar, Mazen A. (Frontiers in Built Environment, 2022)
In general plates are classified as thick plates when the minimum dimension to thickness ratio (b/h) is less than 10. Thin plates when b/h ratio ranges from 10 to about 100 provided that the plate maximum deflection to thickness ratio (w/h) is less than 0.2. Membranes when and w/h ≥ 0.2. Thick plates develop internal stress resultants governed by three-dimensional elasticity similar to that of a solid body. Thin plates behave as plane stress members governed by two-dimensional elasticity. Membranes can only develop internal tensile stresses within the plate neutral plane. Few studies have adopted b/h ratios between 90 to 110 to investigate the feasibility of the utilization of such plates in their various available forms. The current study with b/h ratio of 100 aims to fill the gap. Steel Plates are available in different forms such as intact plates, stiffened, perforated, and stiffened perforated plates. They are used in buildings, bridges, ships, as well as aerospace structures. In this paper, the investigated steel plate has a square shape and is subjected to uniaxial loading. The plate edges are simply supported. The plate is 200 mm wide and 2 mm thick. In this case the critical buckling strength is in general less than the plate maximum strength. With further loading the plate would experience an undesirable sudden mode of failure owing to buckling instability. This study aims at investigating the performance of the different forms of square steel plates, such as intact, stiffened, perforated, and perforated stiffened, when the minimum dimension to thickness ratio is 100. Push over Finite element linear elastic buckling analysis as well as nonlinear large deflection buckling analysis have been carried out. The study indicated that the increase in the plate maximum strength in single, double, triple stiffener plates was 75.6%, 174%, 196% respectively compared to that of the intact plate. Based on the obtained results, it is concluded that the utilization of plates having b/h ratio of 100 is feasible provided that the appropriate plate form is adopted.